Laser hawk - Andor, John ([United States] : Laserbird Films Inc., 1997)
250 millions yeras ago, Aractolds, a carnivorous super-species, introduce embryonic life to a new planet-earth. Their plan-to come back in the distant future and harvest their human crop
Editor, Peter Svab
Starring: Jason James Richter, Melissa Galianos, Gordon Currie, Mark Hamill
VCD format
Keywords: Animals in motion pictures; Aliens in motion pictures; Unidentified Flying Objects in motion pictures